Analisis Pembentukan dan Perubahan Makna Wasei Eigo pada Situs Jejaring Sosial Ameba Blog - Fauzi, Muhamad; Philiyanti, Frida; Retno Lestari, Dwi Astuti (Jurnal Pendidikan Bahasa Jepang Undiksha, 2024)
This study aims to identify the formation, change of meaning, and types of wasei-eigo found in the Ameba blog. The underlying theories are Tsujimura's (2014: 150) Japanese word formation, Irwin's (2011: 143) compound word shortening theory, Chaer's (2013: 140) meaning change theory, and wasei-eigo types according to Shibasaki, et al (2007: 90). The method used is qualitative descriptive method. The data analysis technique applied is translational pairing. The base technique is the technique of sorting out the determining elements (PUP) with the advanced technique of comparative relationship to distinguish (HBB). The analysis yielded 14 wasei-eigo words in the fashion category of Ameba blog. The data consisted of 9 compounds, 3 words experienced shortening type compound truncation, 1-word experienced shortening type morpho-orthographic truncation, and 1-word experienced shortening type compound truncation and ellipsis middle truncation. In the change of meaning, 4 data experienced narrowing, 1 data experienced expansion, and 9 data experienced total change of meaning. Additionally, out of the total data, 5 data involved imizuregata, 4 data involved eigohyougenfuzaigata, and 5 data involved tanshukugata and eigohyougenfuzaigata types